Analisis Penatausahaan Aset Daerah pada Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Rokan Hilir - Astuti, Resti; Museliza, Virna (Policy, Law and Political Research Center, 2024)
This research aims to determine the process of Regional Asset Administration at the Rokan Hilir Regency BPKAD office and the obstacles faced in Regional Asset Administration at the Rokan Hilir Regency BPKAD office. The type of research used is qualitative research with a descriptive approach. Based on the research results, Regional Asset Administration at the Rokan Hilir Regency BPKAD office is based on bookkeeping, inventory and reporting indicators. The implementation of bookkeeping has not gone well because when goods are procured they are not immediately registered and recorded in the inventory book which ultimately causes data gaps on the Goods and Room Inventory Card such as goods codes, year of purchase, and important numbers on official vehicles caused by negligence in recording regional assets used by other parties. Then the implementation of the inventory also did not go well, such as data collection which was not optimal because the whereabouts of the goods were not clear, there were still goods which did not have item code labels because they were damaged and had not been refurbished, and there were still rooms which did not have Room Inventory Cards because they had not been renewed. And the implementation of reporting at the Rokan Hilir Regency BPKAD office has gone well because the submission is always on time. Obstacles in administering regional assets at the Rokan Hilir Regency BPKAD office include a lack of human resources and organizational cooperation as well as lack of orderly administration.